Time, work, and organization - Hassardd, John.; Hill, Stephen.; Starkey, Ken.; Blyton, Paul. (Routledge, 1989)
This book is about: Time and industrial sociology; Time and work: a psychological perspective; Time and work: an economic analysis; Time and organization; Time and labour relations; ...